2017
DOI: 10.1007/s00404-016-4276-6
|View full text |Cite
|
Sign up to set email alerts
|

MR pelvimetry: prognosis for successful vaginal delivery in patients with suspected fetopelvic disproportion or breech presentation at term

Abstract: In our cohort, MR pelvimetry was a useful tool for prepartal assessment of the female pelvis in the selection of TOL candidates. Yet, it does not seem to yield additional predictive value for women with a previous vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 32 publications
0
22
0
2
Order By: Relevance
“…18 Moreover, MR pelvimetry has been shown to be beneficial in suspected fetopelvic disproportion or breech presentation at term. 19,20 One of the limitations of this study is that the measurements were performed after the birth. This prevented from detecting pelvic changes due to the relaxing hormone secreted during pregnancy and identifying the effect of the pelvis on delivery.…”
Section: Discussionmentioning
confidence: 99%
“…18 Moreover, MR pelvimetry has been shown to be beneficial in suspected fetopelvic disproportion or breech presentation at term. 19,20 One of the limitations of this study is that the measurements were performed after the birth. This prevented from detecting pelvic changes due to the relaxing hormone secreted during pregnancy and identifying the effect of the pelvis on delivery.…”
Section: Discussionmentioning
confidence: 99%
“…We did not explore the role of maternal factors and techniques such as sonographic pelvimetry in the need for Cesarean delivery in our patient cohort. Some recent studies have suggested a role for pelvimetry, measured using computed tomography or magnetic resonance imaging, for identification of those at high risk of cephalopelvic disproportion 26,27 . Combining maternal sonographic pelvimetry with fetal adiposity in an effort to assess risk of unplanned intrapartum Cesarean delivery could form the basis of future work.…”
Section: Discussionmentioning
confidence: 99%
“…The use of MR is generally limited by its availability, higher cost, and longer examination time compared to manual examination and ultrasound. However, previous studies indicated that prepartal MR pelvimetry is associated with lower rates of unplanned CS [11,18]. Therefore, it could be argued that MR pelvimetry is justified when supposedly unnecessary CS and associated morbidity can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…MR pelvimetry was performed as previously described [18]. The woman was placed in a supine position in a 1.5-Tesla MR system with a body coil.…”
Section: Mr Pelvimetrymentioning
confidence: 99%